PERANCANGAN GEDUNG MICE KAI CORPORATE UNIVERSITY DENGAN PENDEKATAN ARSITEKTUR ORGANIK - Setyoadi, Maria Renate (Universitas Mercu Buana, 2024)
Organizing Meeting, Incentive, Convention and Exhibition (MICE) events is part of event tourism which is a business with high tourism spending value supported by tourism infrastructure and facilities with special standards. Currently, the city of Bandung is one of the cities in Indonesia which is a destination for holding MICE events. The holding of this MICE event is characterized by frequent business activities such as meetings, seminars, conferences, exhibitions and other activities, both formal and non-formal.Regarding infrastructure and facilities in the form of the MICE Building which will be built by PT. KAI's vision is to develop KAI's human resource competencies through organizing training programs intended for KAI workers, including drivers, conductors, and other railway professions needed to achieve the company's business goals and to face challenges in an ever-changing market.Located on Jalan Laswi, Bandung City, with an organic architectural concept that strengthens the character of the planning land by preserving the function of RTH (Green Open Space) and significant vegetation. Organic architecture is an architectural philosophy that promotes harmony between human habitation and nature, through designs that harmoniously bring together the location of the building, furniture and the environment to become part of one composition, united and interconnected.